Effect of closed-chain isometric plyometric training combined with palonosetron on postoperative knee function in patients after total knee arthroplasty - Shao, Jingwen; Qu, Shaoyi; Wang, Jing; Sun, Dan; Hu, Qing; Luo, Zhongxiang (Frontiers in Surgery, 2025)
BackgroundFunctional training after total knee arthroplasty (TKA) is of great significance for the recovery of knee function. However, the utility of applying an effective training modality, closed-chain isokinetic plyometric training, on top of the drug palonosetron, which is used to prevent nausea and vomiting, is unclear.ObjectiveTo investigate the effect of closed-chain isokinetic plyometric training combined with palonosetron-on-postoperative-knee-function in patients with TKA, aiming to provide an effective rehabilitation program for patients with TKA.MethodsThe results of the intervention were compared in 47 TKA patients who received closed-chain isokinetic plyometric training combined with palonosetron with 47 TKA patients who received conventional plyometric training combined with palonosetron. Knee function was evaluated using the Hospital for Specialty Surgery Knee (HSS), quadriceps muscle strength was assessed using real-time isometric plyometric testing with the BIODEX-sYs-tem 4-type system, walking ability was evaluated using the Timed Up-and-Go Test (TUGT), and proprioception was determined using the Biodex System 4-type multi-joint isometric system.ResultsAfter-the intervention,-the-HSS scores-of-the-experimental-group-were-higher-than-those-of-the-control-group-(P < 0.05); the peak moment values of the quadriceps (PT), the total quadriceps work values (STW), and the average power of the quadriceps (AP) were higher than those of the control group (P < 0.05); and the values of the reproduced deviation of the knee joint active joint angle and the TUGT time were lower than those of the control group (P < 0.05).ConclusionClosed-chain isokinetic plyometric training combined with palonosetron can strengthen their muscle strength and improve proprioception, which effectively promotes the recovery of postoperative knee function and walking ability in TKA patients.